State-Building and Democracy: Prosperity, Representation and Security in Kosovo - Silander, Daniel; Janzekovitz, John (International Studies. Interdisciplinary Political and Cultural Journal, 2012)
The traditional assumption of the state sovereignty norm has been that an international society of states will structure the international order to safeguard the interests of the state. The end of the Cold War era transformed international relations and led to a discussion on how states interacted with their populations. From the early 1990s, research on international relations, war and peace, and security studies identified the growing problem of failing states. Such states are increasingly unable to implement the core functions that define the sovereignty norms. This article explores the state-building process of Kosovo with a focus on the political road taken from independence in February 2008 to the challenges Kosovo faces today. Kosovo still has substantial issues to address regarding core state functions in the development of prosperity, popular representation and security.